Phylogenetics and species delimitation of Lupinus fistulose rosettes : analysis of Colombian populations (2015)
The Andean radiation of Lupinus (ca. 85 species) presents one of the highest rates of net species diversification among island-like systems. The lack of monographic synthesis, uncertainties over species delimitation and the conflicting taxonomy have lead to ambiguities and difficulties in specimen identification. One of the most peculiar growth forms found in the Andean Lupinus are the Fistulose-lnflorescence Rosettes (FIR). Two FIR species found in Colombia, Lupinus triananus C.P.Sm. commonly assigned to populations in the East Cordillera, and Lupinus alopecurotdzs Desr. assigned to populations in both the Central and East Cordilleras, present morphological differences between populations which may lead to taxonomic recircumscription. In this study we used genome-scale DNA sequence data generated from (RAD) markers to estimate the phylogenetic relationships among FIR populations from the Northern Andes in the context of the Andean radiation as a whole.